A cavitating device for mini quantitative liquid addition. (October 2017) - Zhu, Xiaolong; Wang, Deming; Wang, Hetang; Zhu, Yunfei; Xu, Chaohang
Abstract: To improve accuracy and stability of mini quantitative liquid adding, a new cavitating venturi device is proposed and investigated experimentally. Cavity cloud initiates at the throat exit where the velocity gradient is the highest and the local pressure is the lowest. Since the suction inlet is set at the throat exit, it is easily covered by the cavity cloud in which the pressure remains at saturation vapor pressure. Once cavity cloud dominates the suction inlet, both working and suction flow rate remains constant and independent of downstream pressure. Therefore, the proposed device can be used as an adding device and a flow meter simultaneously when it is under cavitation condition. The critical pressure ratio exceeds 0.6 when flow ratio is below 2%, which is over 50% higher than present jet pumps. The critical pressure ratio rises with the decreasing of adding ratio, which makes the proposed adding device especially applicable for mini quantitative adding. Moreover, the working range of the proposed device is hardly changed when sucked water is replaced by high-viscosity foaming agent. Highlights: The proposed device has a wider cavitating working range than present jet pumps. The proposed device can simultaneously work as an adding device and a flow meter under operating limits. The adding liquid with different viscosity hardly affect the working range of cavitation condition.